2012
DOI: 10.1021/ef3012382
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel from Microalgae, Yeast, and Bacteria: Engine Performance and Exhaust Emissions

Abstract: Biodiesels (fatty acid methyl esters) derived from oleaginous microbes (microalgae, yeast, and bacteria) are being actively pursued as potential renewable substitutes for petroleum diesel. Here, we report the engine performance characteristics of biodiesel produced from a microalgae (Chaetoceros gracilis), a yeast (Cryptococcus curvatus), and a bacteria (Rhodococcus opacus) in a two-cylinder diesel engine outfitted with an eddy current brake dynamometer, comparing the fuel performance to petroleum diesel (#2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(78 citation statements)
references
References 51 publications
4
74
0
Order By: Relevance
“…These results indicate that, due to substantial differences in the specific gravities of the evaluated fuels, one should also consider the energy capacity expressed per volume of fuel when assessing fuel consumption (Lapuerta et al, 2011). The findings of this study relative to fuel consumption are in general agreement with the findings for FAME (Graboski and McCormick, 1998; Wahlen et al, 2013; Kim et al, 2014) and HVORD fuels (Kim et al, 2014). …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These results indicate that, due to substantial differences in the specific gravities of the evaluated fuels, one should also consider the energy capacity expressed per volume of fuel when assessing fuel consumption (Lapuerta et al, 2011). The findings of this study relative to fuel consumption are in general agreement with the findings for FAME (Graboski and McCormick, 1998; Wahlen et al, 2013; Kim et al, 2014) and HVORD fuels (Kim et al, 2014). …”
Section: Resultssupporting
confidence: 89%
“…FAME biodiesel fuels are obtained from various plant and algae oils and from animal fats through the process of transesterification (Graboski and McCormick, 1998; Wahlen et al, 2013). The chemical and physical properties of FAME fuels are highly dependent on feedstock: for example, FAME biodiesel produced from soybean oil is primarily made up of unsaturated oleic and linoleic fatty acid while the biodiesel produced from palm oil is primarily made up of saturated palmitic and unsaturated oleic fatty acid.…”
Section: Introductionmentioning
confidence: 99%
“…Biodiesel, derived from oil or fats, is ideal for the heavy transportation and aviation markets. A number of studies showed that microbial lipids prepared from oleaginous yeasts, bacteria, and microalgae could be employed to produce biodiesel of comparable properties with those made from typical plant oils (Liu and Zhao, 2007;Wahlen et al, 2013). Thus, it is currently considered as the potential feedstock for biodiesel (Meng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The experiments showed that both strains can consume these carbon sources and accumulate lipids close to 20 % of their own weight. With regard to bacterial biodiesel properties and subsequent engine testing, only one analysis has been reported (Wahlen et al 2012). In this study, the bacterium R. opacus was grown in sucrose and biodiesel properties were compared with those from microalgae and yeast oil-based biodiesel.…”
Section: Bacteriamentioning
confidence: 99%
“…Although it varies depending on the species and substrate, it is mostly composed of palmitic and oleic acid, the latter being preferred for the biodiesel industry due to its high unsaturation degree (Pinzi et al 2011). Wahlen et al (2012) compared biodiesel properties, performance, and emissions in a diesel engine, biodiesel being produced from soybean, algae, bacteria, and yeast oil. Only small differences in terms of exhaust emissions were detected, as biodiesel from yeast oil emitted lower hydrocarbon but higher NO x emissions.…”
Section: Yeastmentioning
confidence: 99%